Anatomical and pathological diagnosis of genetic diseases in Gynecology and Obstetrics - Pereda, José (2015)
Examples of genetic diseases that may be identified by studying biopsy specimens and necropsies samples are presented. It is emphasized that diagnosis of these cases will allow genetic counseling for affected families. The importance of pathology studies in the protection of family health is emphasized .